Nanofabrication of Losartan Potassium Sustained Release Floating Microspheres using Different Grades of Ethyl Cellulose and its Insight on Release Profiles - Rajput, Tanavirsing; Mohite, Popat; Ghule, Santosh; Vinchurkar, Kuldeep; Singh, Sudarshan (Current Pharmaceutical Design, 2024)
Introduction: A sustained release system for losartan potassium designed to delay its residence time in the stomach through the preparation of solvent evaporation technique-based floating microspheres. The influence of the different grades of Ethocel™ such as 4 cps, 10 cps, and 22 cps as well as the drug: polymer ratio on various properties of microspheres were tested. Methods: Thermal and functional analysis revealed no interaction between the encapsulated drug and polymer. The results indicated that the mean diameter of microspheres increased with a change in grades of ethyl cellulose relating to viscosity. However, the drug incorporation efficiency within ethyl cellulose microspheres decreased with increasing viscosity of ethyl cellulose. Results: The bulk density of the formulations was proportionally dependent on concentration and the viscosity of the polymer, which resulted in a decrease in floating capacity from 90.02% to 73.58%. Moreover, the drug release was indirectly proportional to the viscosity of ethyl cellulose tested. The in vitro release profile exhibited a burst effect with a biphasic release pattern following Fickian diffusion, indicating a diffusioncontrolled release mechanism. Conclusion: The results demonstrated that the viscosity of ethyl cellulose significantly affects the floating capacity and drug release pattern from microspheres.
Keywords: solvent evaporation